UP element-dependent transcription at the Escherichia coli rrnB P1 promoter: positional requirements and role of the RNA polymerase α subunit linker - Meng, Wenmao (Oxford University Press, 2001)
The UP element stimulates transcription from the rrnB P1 promoter through a direct interaction with the C-terminal domain of the RNA polymerase α subunit (αCTD). We investigated the effect on transcription from rrnB P1 of varying both the location of the UP element and the length of the α subunit interdomain linker, separately and in combination. Displacement of the UP element by a single turn of the DNA helix resulted in a large decrease in transcription from rrnB P1, while displacement by half a turn or two turns totally abolished UP element-dependent transcription. Deletions of six or more amino acids from within the α subunit linker resulted in a decrease in UP element-dependent stimulation, which correlated with decreased binding of αCTD to the UP element. Increasing the α linker length was less deleterious to RNA polymerase function at rrnB P1 but did not compensate for the decrease in activation that resulted from displacing the UP element. Our results suggest that the location of the UP element at rrnB P1 is crucial to its function and that the natural length of the α subunit linker is optimal for utilisation of the UP element at this promoter.